Juridical Review Of The Customary Sale And Purchase Of Land In Kalisalak Village, Limpung District, Batang District - Sihotang, Amri Panahatan; Udianto, Udianto - (Faculty of Law, Universitas Pekalongan, 2024)
A reform intended to ensure legal certainty and improve the quality of evidence is the sale and purchase of land, which was previously sufficient to be completed in the presence of the village head but now needs to be completed in the presence of the PPAT per land regulations. The issue at hand pertains to the proper methods for purchasing and disposing of customary land within Kalisalak village, as well as the challenges that may arise. This study employed an empirical juridical research design with analytical descriptive research criteria. The study's findings indicate that, despite certain barriers to customary land purchasing and selling, the community's continued practice of land transactions based on custom is still permitted as long as the